Eosinophilic pancreatitis: a rare or unexplored disease entity? - Murli Manohar; Alok Verma; Gulshan Singh; Anil Mishra (Gastroenterology Review)
Several case reports show accumulation of eosinophils in pancreatitis patients and term the disease as “eosinophilic pancreatitis (EP)”. EP usually presents with a pancreatic tumour and abdominal pain in obstructive jaundice, which is generally not diagnosed until the patient undergoes pancreatic resection. Histologically, EP reveals distinct patterns like diffused, periductal, acinar, and septal inflammatory infiltrates with eosinophils, eosinophilic phlebitis, and localised extreme eosinophilic infiltrates related with pseudocyst formation. EP patients also have elevated serum IgE levels with high eosinophil counts in the pancreas as well as in other organs such as the gastrointestinal tract, which is termed as eosinophilic gastroenteritis. Due to the lack of knowledge based on just a few case reports, it is considered that eosinophilic infiltration is quite rare in the pancreas; therefore, the significance of eosinophils in pancreatitis is not yet established. This review assesses the current understanding of eosinophilic pancreatitis and the important role of eosinophils in promoting pancreatic fibrosis including malignancy.